Peningkatan Kapasitas Guru Dan Siswa Untuk Meningkatkan Kualitas Pembelajaran - Rahmiati Darwis; Muhammad Rizal Hardiansyah; Nurwafiah Marda; Wa Ode Hamida (IAIN AMBON, 2023)
The PhET (Physics and Education Technology) virtual laboratory is an interactive medium of science with the help of computer applications that contains simulations of natural science experiments. The purpose of this activity is to increase the interest and motivation in learning science for elementary school (SD) students and to enrich the knowledge and skills of teachers and students in using science learning media through virtual PhET simulations. This activity was attended by 40 students using lecture methods, discussions, practical applications of PhET interactive simulations. Learning natural sciences using the PhET virtual laboratory was able to arouse students' interest and motivation in learning natural sciences.Keywords: Virtual Laboratory, PhET